Multiproxy analysis unwraps origin and fabrication biographies of Sardinian figurines: On the trail of metal-driven interaction and mixing practices in the early first millennium BCE - Daniel Berger; Valentina Matta; Nicola Ialongo; Heide W. Nørgaard; Gianfranca Salis; Michael Brauns; Mads K. Holst; Helle Vandkilde (PLoS ONE, 2025)
This article presents a multiproxy investigation of metal samples obtained from 48 Nuragic figurines (so-called bronzetti) and three copper bun ingots. These objects originate from three prominent Sardinian sanctuaries and one unidentified site, dating to the late Nuragic period of the early first millennium BCE. The dataset significantly expands the existing scientific database and unwraps the complex fabrication biographies of the figurines from ore to finished object. The investigation employs an advanced archaeometallurgical approach, integrating conventional trace-elemental and lead isotope analyses with rarely used copper, tin, and osmium isotope measurements. This methodological combination allows for a more reliable identification of the original metal sources used in the production of the objects, namely copper from the Iglesiente-Sulcis district in southwest Sardinia, with the Sa Duchessa mine as the most likely supplier, in addition to copper from the Alcudia valley or the Linares district in the Iberian Peninsula. Notably, the combination of analytical proxies reveals the mixing of copper from these distinct regions, while ruling out the exploitation of Sardinian tin resources. Furthermore, the osmium isotope ratios confirm the use of Sardinian copper and exclude the alloying of local lead with imported copper. These results shed light on local metallurgical practices and distribution strategies in Nuragic Sardinia, but also on Sardinia’s broader role and position in the Mediterranean world during the transition from the Late Bronze Age to the Early Iron Age.